KETERDAPATAN DAN TIPE MINERAL PADA BATUBARA SERTA METODE ANALISISNYA - Edy Nursanto; Arifudin Idrus; Donatus Hendra Amijaya; Subagyo Pramumijoyo (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2011)
Coal is sediment composed by organic and inorganic materials with organic contents that more than 50%.The organic matters are derived from the remaining plants and have been decomposition and changes in physical and chemical properties. Based on their abundance, then the minerals in coal can be divided into primary minerals (major minerals), extra minerals minor minerals) and trace minerals. Consist of the major minerals are clay minerals and quartz while the minor minerals are carbonates, sulfides and sulfates. Analysis that used for mineral in coal is Microscopic optical, Scanning Electron Microscopic (SEM), Electron Probe Micro Analyzer (EPMA), and x-ray Diffraction (XRD).